IoT based reconfigurable smart city architecture - Geetha Pratyusha, M; Misra, Yogesh; Anil Kumar, M (International Journal of Engineering and Technology, 2018)
Now-a-days Internet of Things is deployed almost in every application regarding smart cities and have been initiated to develop all over the world. Smart Devices are being geared up to ease human life. Due to the growth in Internet of Things technology, smart cities are been developedwith this technology to work with the issues of public as well as private. The aim of the article is to enhance a solution to the problems in the smart cities with latest IoT architecture, protocols and services. With the technical support of IoT, using low power Wireless Sensor Networks (WSN) which is connected to transfer the data from M2M applications. In addition to the IoT, intelligent features are integrated with the help of Computer vision makes the technology more flexible. The goal of this article is to engrave the services to challenge the real time environment with low power synthesis technique. Only then, the smart city features are improved and serves the mankind with IoT technology.